2013
DOI: 10.1016/j.jhep.2013.02.020
|View full text |Cite
|
Sign up to set email alerts
|

PEPCK-M expression in mouse liver potentiates, not replaces, PEPCK-C mediated gluconeogenesis

Abstract: Background & Aims Hepatic gluconeogenesis helps maintain systemic energy homeostasis by compensating for discontinuities in nutrient supply. Liver specific deletion of cytosolic phosphoenolpyruvate carboxykinase (PEPCK-C) abolishes gluconeogenesis from mitochondrial substrates, deregulates lipid metabolism and affects TCA cycle. While, mouse liver almost exclusively expresses PEPCK-C, humans equally present a mitochondrial isozyme (PEPCK-M). Despite clear relevance to human physiology, the role of PEPCK-M and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 46 publications
2
90
0
2
Order By: Relevance
“…However, PF-4708671 failed to significantly reduce PEPCK or G6Pase protein expression despite lower mRNA expression of these enzymes. It is possible that G6Pase and PEPCK proteins are only reduced in specific cellular compartments [38][39][40]. Indeed, we have used a PEPCK1-specific antibody that recognises the cytosolic isoform, whereas PEPCK2 is predominantly a mitochondrial form.…”
Section: Discussionmentioning
confidence: 99%
“…However, PF-4708671 failed to significantly reduce PEPCK or G6Pase protein expression despite lower mRNA expression of these enzymes. It is possible that G6Pase and PEPCK proteins are only reduced in specific cellular compartments [38][39][40]. Indeed, we have used a PEPCK1-specific antibody that recognises the cytosolic isoform, whereas PEPCK2 is predominantly a mitochondrial form.…”
Section: Discussionmentioning
confidence: 99%
“…Rodents should not be considered PEPCK-M knockouts especially when interpreting data from PEPCK-C knock-out mice (11)(12)(13)39). It is important to point out that both isoforms depend on mitochondrial metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Whole body loss of PEPCK-C increases hepatic TCA cycle intermediates and reduces oxidation of glucose, acetate, and glutamate between 65 and 80% (12,28). Recently, 100-fold hepatic overexpression of PEPCK-M in liver-specific knockouts of PEPCK-C had no measureable consequence in vivo and only a marginal improvement (ϳ8%) of PEP gluconeogenesis in vitro (39). The interpretation was that PEPCK-M has a minimal supportive role in gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A possible role for PEPCK-M in insulin secretion has been suggested (31). A recent report (32) showed that overexpression of PEPCK-M in mice in which hepatic PEPCK-C was deleted partially rescued defects in glucose production. Furthermore, the two enzymes were shown to be independently regulated.…”
mentioning
confidence: 99%